Dados brasileiros do mundo real sobre imunoterapia em câncer de pulmão de células pequenas com doença extensa - Flávia Amaral Duarte (2024)
Background: The landmarks of thoracic Oncology in the last two decades have been accompanied by exponential growths in costs, which makes imperative the assessment of the real benefit of new technologies incorporations, particularly those with marginal gains. The combination of immunotherapy (IO) with platinum-etoposide chemotherapy has become the standard of care in first-line treatment of extensive stage small cell lung cancer (ES-SCLC), although the absolute difference in median overall survival (OS) has reached three months. This study aimed to investigate the impact of this intervention in a real-world cohort of a middleincome country. Objetivies and methods: We retrospectively analyzed data from all ES-SCLC patients from Oncoclinicas, the largest community oncology practice in Latin America, diagnosed and treated between January 2018 and June 2022. Primary objectives were median OS (mOS) and median time to next treatment (mTNT) according to IO exposure in the first-line setting. Secondarily, we intent to compare these results with an internal and contemporary cohort of patients treated with chemotherapy alone. Relevant clinical characteristics which might impact the results were also evaluated. The project was approved by local Ethics Committee. Results: Eighty-five patients with SCLC were included in this analysis. The median age was 69 years, 49% were male, 57% had smoking history, and only 10% had ECOG 2-3. At diagnosis, 80% presented with ES-SCLC and 20% had central nervous system metastasis. First line regimens were atezolizumab + platinum-etoposide in 53%, platinum-etoposide in 36% and platinum-irinotecan in 11%. Median follow-up was 9.0 months. Among ES-SCLC pts who received IO in their first-line treatment, median mOS was 15.0 months (95 CI: 11.20; 18.80) compared to 9.0 months (95 CI: 2.08; 19.92) in those who did not receive IO (p = 0,672). Median TNT of the first line IO was 8.0 months (95 CI: 6.25; 9.75) compared to 8.0 months (95 CI: 5.88; 8.12) of those who received chemotherapy only (p = 0,759). Conclusions: There are few real-world cohorts evaluating the impact of IO in ES-SCLC and they are limited to high-income countries. Our data suggest that IO may have a meaningful impact in the outcome of ES-SCLC in in a real-world setting of a middle-income country, with median OS comparable to clinical trials. Larger sample, longer follow-up as well as prospective analysis may add more robust evidence.